A survey of the cytotoxicity of some medicinal plant extracts in Ghana against breast and prostate cancer cells - Kwadwo Fosu; Bridget Agbesi; Richard Gyan; Ebenezer Eduam Afful; Fussein Hussein; Daniel Takyi; Eric Frimpong; Ann Deborah Darko; Cosmos Nuer; Joshua Nsiah; Divine Yao Sapey; Foster Kyei (Clinical Phytoscience)
Abstract Cancer remains a global health challenge, with breast and prostate cancers being significant contributory factors to morbidity and mortality. Current treatments are limited by high costs, resistance, and adverse effects hence prompting the exploration of alternative therapies. This study evaluated the anticancer potential of crude extracts of ten medicinal plants commonly found in Ghana: Azadirachta indica, Vernonia amygdalina, Launaea taraxacifolia, Dissotis rotundifolia, Chromolaena odorata, Heliotropium indicum, Zingiber officinale, Carica papaya (leaves and seeds), and Solanum melongena, in breast (MCF-7) and prostate (PC-3) cancer cell lines. The plants were collected, authenticated, and processed for ethanolic extraction. Phytochemical analysis identified bioactive compounds including alkaloids, flavonoids, phenols, tannins, saponins, terpenoids, and glycosides. The cytotoxicity assays revealed a dose-dependent reduction in cell viability, with greater effects observed at higher concentrations than at lower concentrations. The extracts were found to be very effective even after 24 h hours, indicating their highly potent nature for these plants. Notably, extracts from Heliotropium indicum, Vernonia amygdalina, and Azadirachta indica showed significant activity, which could be attributed to their alkaloids and terpenoids, which induce apoptosis and inhibit proliferation. These findings highlight the therapeutic potential of plant-derived compounds as promising candidates for anticancer drug development. These results also highlight the importance of biodiversity conservation and the integration of traditional knowledge into modern research to combat the global cancer burden. Future studies should focus on optimizing the use of these bioactive compounds, both individually and in combination, to develop more effective cancer treatments.